Taxonomic studies and three new records on genus Geostachys (Baker) Ridl. in Thailand - Piyaporn Saensouk; Surapon Saensouk (Society for Indonesian Biodiversity, 2021)
Abstract. Saensouk P, Saensouk S. 2021. Taxonomic studies and three new records on genus Geostachys (Baker) Ridl. in Thailand. Biodiversitas 22: 3057-3067. A comprehensive taxonomic study and three new records of genus Geostachys (Baker) Ridl. in Thailand have not been reported. This research aimed to study the taxonomical aspect of the genus Geostachys in Thailand based on herbarium collections, fresh materials, and available literatures. Nine species of Geostachys have been recognized with their updated nomenclature in Thailand, namely G. angustifolia K. Larsen, G. chayanii Mayoe, G. decurvata (Baker) Ridl., G. holttumii K. Larsen, G. kerrii K. Larsen, G. penangensis Ridl., G. pierreana Gagnep., G. smitinandii K. Larsen, and. G. tratensis Picheans. & Mayoe. Three species, namely G. decurvata, G. pierreana, and G. penangensis are found to be new records to Thailand. Six species, namely G. angustifolia, G. chayanii, G. holttumii, G. kerrii, G. smitinandii, and G. tratensis were endemic to Thailand. The identification key to species, detailed descriptions, photographs, vernacular name, geographical distribution, ecology, phenology, conservation status, and taxonomic notes have been provided.